CEO pay incentives and risk-taking: Evidence from bank acquisitions - Hagendorff, Jens; Vallascas, Francesco (Journal of Corporate Finance, 2011)
We analyze how the structure of executive compensation affects the risk choices made by bank CEOs. For a sample of acquiring U.S. banks, we employ the Merton distance to default model to show that CEOs with higher pay-risk sensitivity engage in risk-inducing mergers. Our findings are driven by two types of acquisitions: acquisitions completed during the last decade (after bank deregulation had expanded banks' risk-taking opportunities) and acquisitions completed by the largest banks in our sample (where shareholders benefit from ‘too big to fail’ support by regulators and gain most from shifting risk to other stakeholders). Our results control for CEO pay–performance sensitivity and offer evidence consistent with a causal link between financial stability and the risk-taking incentives embedded in the executive compensation contracts at banks.